Room monitoring system using radio frequency (RF) technology and passive infrared sensor (PIR) - Abros Noori, Anvardeen (2008)
Room monitoring system using Radio frequency (RF) technology and Passive Infrared Sensor (PIR) is a solution for the electricity wastage. In this project PIR used because this device is still new in market and not widely explored by users. This device act as an automatic switch, the light will automatically on when there is presence of intruders in monitored area. Monitoring system also combined to this project where, a signal will be send to monitoring room to indicate the presence of person in monitored area. The signals send to the monitoring room using Radio Frequency and turn on the indicator for monitored area. The designed circuit will be implemented and a simple application of wireless communication will be demonstrated using the PIC microcontroller to transfer streams of data and for control and data processing.